3(3+4x)-3=66

Simple and best practice solution for 3(3+4x)-3=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3+4x)-3=66 equation:


Simplifying
3(3 + 4x) + -3 = 66
(3 * 3 + 4x * 3) + -3 = 66
(9 + 12x) + -3 = 66

Reorder the terms:
9 + -3 + 12x = 66

Combine like terms: 9 + -3 = 6
6 + 12x = 66

Solving
6 + 12x = 66

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 12x = 66 + -6

Combine like terms: 6 + -6 = 0
0 + 12x = 66 + -6
12x = 66 + -6

Combine like terms: 66 + -6 = 60
12x = 60

Divide each side by '12'.
x = 5

Simplifying
x = 5

See similar equations:

| x^2+37x+36= | | 7x-6x=70 | | 8x-(6x+6)=2 | | 10-(2x-5)=3(4x-2)-(5x-8) | | -3(x+1)+4x=10 | | x/3+26=25 | | 8x-(3x+4)=12 | | 3x^2-26x=-2x-7x-12 | | 4t-t-8=2t-4 | | 42=-5x+2 | | 6k+k+4=25 | | 4(6t+2)=80 | | 4(6t+2)=55 | | -31-4x=-5-(1+5x) | | (4a-3b+c-5d)5= | | 4(6t+2)=54 | | 4x+x-5=4x+4 | | 4(6t+2)=52 | | -2(21y)= | | 4(6t+2)=53 | | 4(6t+2)=60 | | -2x=-2+8 | | 5x-6=-81 | | 4(6t+2)=4 | | 5x+12-9x=19-15x+11x-7 | | 7x-6x+4x-9x= | | 9+8q=11+7q | | 4(6t+2)=50 | | 4(6t+2)=40 | | 4(6t+2)=28 | | -22(a+6)=-22 | | -3x-2=25 |

Equations solver categories